The 1984 Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (UNCAT) - Stejskal, Petr; Faix, Martin (The Universal Protection of Human Rights, 2026)
Abstract: The chapter provides a comprehensive analysis of the 1984 Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (“UNCAT”), focusing on its legal context, key provisions, and the challenges in implementing its obligations. The UNCAT, a cornerstone of international human rights law, addresses the prohibition and prevention of torture by articulating specific duties for States Parties, including the criminalisation of torture, providing redress for victims, and ensuring universal jurisdiction over offenders. The chapter delves into the historical backdrop of torture and the legal developments that led to the adoption of the UNCAT, emphasising its importance in strengthening the prohibition of torture, which was already recognised in customary international law. The chapter further explores the structure of the UNCAT, focusing on its substantive obligations, such as the principle of non-refoulement, the duty to investigate and prosecute acts of torture, and the establishment of a monitoring body, the Committee against Torture. It also highlights issues with implementation of the prohibition of torture and explains the relevance of the Optional Protocol to the Convention, which introduced new mechanisms for preventing torture through national preventive measures and regular monitoring visits. In addition to explaining the legal framework of the Convention, the chapter includes a selection of key cases, particularly those involving Central and Eastern European States, which have shaped the interpretation and enforcement of the UNCAT provisions. These cases demonstrate the evolving understanding of the obligations under the UNCAT and the importance of state accountability in the fight against torture.Keywords: torture, ill-treatment, universal jurisdiction, country-visit, Committee against Torture